ANALISIS KUALITAS SNACK BAR FORMULASI TEPUNG KACANG TUNGGAK DAN IKAN BANDENG SEBAGAI MAKANAN SELINGAN TINGGI ZAT BESI BAGI REMAJA PUTRI - Yuliati Dewi, Yusrina; Judiono, Judiono; Mahmudah, Umi; Hastuti, Widi; Mulyo, Gurid PE (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2022)
Snack bar milkfish cowpea is a snack with the main raw materials, cowpea flour, and milkfish flour. Snack bars are needed for young women, which can be useful in increasing iron and protein so that they can prevent iron anemia. This study aimed to determine the formulation snack bar of milkfish cowpea according to organoleptic properties, protein, and iron content with an experimental study research design with a Completely Randomized Design (CRD). The research used a hedonic test to determine organoleptic properties, atomic absorption spectrophotometry (AAS) for the iron test, and micro Kjeldahl for the protein test. The formulation snack bar consists of three balances: the 90%:10% formula, the 80%:20% formula, and the 70%:30% formula. The organoleptic statistical tests showed no differences in color, aroma, taste, and texture. The 90%:10% formula is superior in color, aroma, taste, and texture. The iron content in the formula 90%:10%, formula 80%:20%, and formula 70%:30% resulted in 1.8602 ppm, 1.5765 ppm, and 1.3313 ppm. The protein content of the formula 90%:10%, formula 80%:20%, and formula 70%:30% are 8.0669%, 8.8988%, and 9.6619%. Further research is needed on the effectiveness of giving snack bars to young women.